Faktor- Faktor yang Mempengaruhi Tingkat Bagi Hasil Deposito Mudharabah pada BMT Maslahah Se-Kabupaten Situbondo - Yulinartati Yulinartati; Diyah Probowulan; Tara Ayu Adevia Putri (Jurnal Ekonomi Akuntansi dan Manajemen, 2020)
The level of profit sharing provided by Islamic banks is one of the public's attractions to store funds in Islamic banks, but at the profit sharing level. Because it still refers to conventional bank interest rates, people still think that Islamic banks are the same as conventional banks. This study aims to analyze the factors that influence the level of profit sharing of mudharabah deposits at BMT Maslahah in Situbondo Regency. The population used is the annual financial statements in the 5 Sub-District Regencies of Situbondo 2014-2019. The sample selection tested in this study used SPSS 20.0 software. Variables used in this study are Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposits Ratio (FDR), BOPO (Operational Costs Operating Income). As an independent variable, and the level of profit sharing of mudharabah deposits as the dependent variable. Some of the results show that the Return on Assets (ROA), Financing to Deposits Ratio (FDR) have a positive effect on the profit sharing rate of mudharabah deposits while Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), BOPO (Operational Cost of Operating Income) has a negative effect . Keywords: Return on Assets (ROA), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposits Ratio (FDR), BOPO (Operational Costs, Operating Income, Profit Sharing Rate for Mudharabah Deposits).